PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH SISWA KELAS VII DI SMP NEGERI 26 MAKASSAR - Aisyah; Aliem Bahri; Mudeing Jais (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Research on the application of the Problem Based Learning learning model to student learning outcomes in history subjects for class VII students at SMP Negeri 26 Makassar. The main problem in this research is to determine the application of the Problem Based Learning learning model to the learning outcomes of class VII students at SMP Negeri 26 Makassar. This research aims to determine the results of student learning at SMP Negeri 26 Makassar and the impact of implementing the Problem Based Learning learning model on student learning outcomes in history subjects for class VII students at SMP Negeri 26 Makassar. This type of research is qualitative research. The research procedure was carried out in the stages of observation, interviews and documentation. Data sources were taken from observations, interviews and documentation with school principals, teachers and students. The research results show that the application of the Problem Based Learning model is a model that is able to solve problems and the learning delivered by the teacher is very effective because this model really provides enthusiasm which can solve a problem. Apart from that, it trains students to think critically, analytically and comprehensively in responding to the problems they face. Based on the results of research with the application of the Problem Based Learning learning model to student learning outcomes in history subjects for class VII students at SMP Negeri 26 Makassar, it is clear that the Problem Based Learning method is still effectively used by teaching staff in achieving the goals or outcomes of student learning and is very It is good to use as a learning method because this method really encourages students to be active and able to learn independently.